The social and capitalism do not exist: the challenge of Bruno Latour - Rochabrún Silva, Guillermo (2015)
Bruno Latour, a former philosopher who turned to anthropology and sociology, whose work is so much known as controversial, has been developing a radical restatement of contemporary social sciences,with broad consequences for them, and in particular for sociology. Stating that the social does not exist, Latour claims the inclusion as «actants», as well as humans, of all kind of objects. According to Latour, in that way it would not be necessary to appeal to transcendent instances of experience, like huge historical processes, or entities in which a specific agent does not appear. After discovering Gabriel Tarde’s scientific production, who is considered by him as an antecessor of his ideas, Latour has lay down both a critique to the homo economicus, as well as to Marx’s vision on capitalism. This article intends to evaluate those critiques, making each author question the other.